Enhanced Recovery after Surgery in Breast Reconstruction: A Systematic Review - Soteropulos, Carol E.; Tang, Sherry Y.Q.; Poore, Samuel O. (Journal of Reconstructive Microsurgery, 2019)
Background Enhanced Recovery after Surgery (ERAS) principles have received focused attention in breast reconstruction. Many protocols have been described in the literature for both autologous and alloplastic reconstruction. This systematic review serves to better characterize successful ERAS protocols described in the literature for potential ease of adoption at institutions desiring implementation.Methods A systematic review of ERAS protocols for autologous and alloplastic breast reconstruction was conducted using Medline, the Cochrane Database, and Web of Science.Results Eleven cohort studies evaluating ERAS protocols for autologous (n = 8) and alloplastic (n = 3) breast reconstruction were included for review. The majority compared with a retrospective cohort of traditional perioperative care. All studies described the full spectrum of implemented ERAS protocols including preoperative, intraoperative, and postoperative phases of care. Most frequently reported significant outcomes were reduced length of stay and opioid use with ERAS implementation. No significant change in major complication or readmission rate was demonstrated.Conclusion Based on this systematic review, several core elements that make up a successful perioperative enhanced recovery protocol for breast reconstruction have been identified. Elements include patient counseling and education, limited preoperative fasting, appropriate thromboprophylaxis and antibiotic prophylaxis dependent on reconstructive method, preoperative antiemetics, multimodal analgesia and use of local anesthetic, goal-directed intravenous fluid management, prompt removal of drains and catheters, early diet advancement, and encouragement of ambulation postoperatively. Implementation of ERAS protocols in both autologous and alloplastic breast reconstruction can positively enhance patient experience and improve outcomes by reducing length of stay and opioid use, without compromising successful reconstructive outcomes.
Keywords: breast reconstruction; enhanced recovery; Enhanced Recovery after Surgery; early discharge protocols; alloplastic breast reconstruction; autologous breast reconstruction